2012
DOI: 10.1152/jn.00748.2011
|View full text |Cite
|
Sign up to set email alerts
|

Observed effector-independent motor learning by observing

Abstract: Williams A, Gribble PL. Observed effector-independent motor learning by observing. J Neurophysiol 107: 1564 -1570, 2012. First published December 21, 2011 doi:10.1152/jn.00748.2011pelling idea in cognitive neuroscience links motor control and action observation. Recent work supports the idea that a link exists not just between action observation and action planning, but between observation and motor learning. Several studies support the idea that cortical regions that underlie active motor learning also play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
5
16
2
Order By: Relevance
“…Only if a movement is hard to learn would we predict that marking facilitates projection by enabling dancers to bring to mind movements that are more detailed or precise than they can mentally simulate while lying down. This is consistent with the findings of Cross et al [2009] and Williams and Gribble [2012]. Both found that subjects who simply observed other people performing a dance movement were able to learn that movement comparably to those practicing the movement fullout themselves.…”
Section: Theoretical Ideas That Might Explain Why Marking Is So Effecsupporting
confidence: 92%
“…Only if a movement is hard to learn would we predict that marking facilitates projection by enabling dancers to bring to mind movements that are more detailed or precise than they can mentally simulate while lying down. This is consistent with the findings of Cross et al [2009] and Williams and Gribble [2012]. Both found that subjects who simply observed other people performing a dance movement were able to learn that movement comparably to those practicing the movement fullout themselves.…”
Section: Theoretical Ideas That Might Explain Why Marking Is So Effecsupporting
confidence: 92%
“…This behavioral difference was seen in the first block of the test FF movements, during which subjects who had observed left FF learning exhibited 40% greater trajectory curvature than control subjects [t(28) ϭ 2.99, P Ͻ 0.03]. This result is consistent with previous observational learning studies (Bernardi et al 2013;Brown et al 2009;Mattar and Gribble 2005;Williams and Gribble 2012).…”
Section: Experiments 1: Motor Learning By Observingsupporting
confidence: 88%
“…A forward model might be indifferent to which limb is involved but contain a pointer back to the source of the command: "Whichever arm you commanded to reach for your hat will not go high enough." (There is some evidence of the existence of functionally specialized neural areas that represent actions in a limb-independent way [Butterfill and Sinigaglia 2012;Cattaneo et al 2010;Chaminade et al 2005;Rijntjes et al, 1999;Williams and Gribble 2012]; granted, this work is not concerned with forward models, or activity of cerebellum, which is thought to be the site of forward models [Grush 2004, 385], but it is at least suggestive.) The relation to CO seems clearer.…”
Section: B Forward Models Efference Copy and Predictive Codingmentioning
confidence: 99%